Az 1944 novemberében-decemberében Budapesten felavatott debreceni doktorok - Mudrák, József (Gerundium, 2015)
INAGURATION OF DOCTORS IN DEBRECEN IN NOVEMBER AND DECEMBER OF 1944. After war had reached the István Tisza University in Debrecen in October 1944, the majority of the professors led to Budapest where they held several meetings. Doctors, who had received their degree earlier, were inagurated in Budapest between November 4 and December 20 in the name of the Debrecen University (23 medical, 3 law, 3 political science, 2 arts doctorate certiicates were given). he partly oicial operation in Budapest lasted until the second part of December, while some of the professors in Budapest, some in rural areas waited out the end of the ights. Some, though, had joined the medical training in Halle and Breslau organized by András Csilléry appointed government commissioner.